The prevalence and burden of four major chronic diseases in the Shanxi Province of Northern China - He, Lu; La, Yuanyuan; Yan, Yan; Wang, Yuxiao; Cao, Xi; Cai, Yutong; Li, Sitian; Qin, Mengxia; Feng, Qilong (Frontiers in Public Health, 2022)
Background: Chronic non-communicable diseases constitute an important public health problem that is closely related to behavioral risk factors. The study examined the prevalence, burden, and behavioral risk factors relevant to four major chronic diseases in Shanxi province, China. The results obtained could provide a basis for the formulation of chronic disease prevention and control strategies in north China. Methods: A multi-stage random sampling method was used to select 14,137 residents aged ≥15 years who completed a questionnaire survey and physical examination. The disease burden was evaluated using the disability-adjusted life years (DALY) index. The extent of disease burden attributable to smoking and drinking behavior was analyzed using counterfactual analysis. Results: The total DALYs due to the four major chronic diseases was 938,100. The years of life lost due to stroke accounted for 74.86%; the years of life lived with disabilities accounted for 54.0% and 68.1% of the total disease burden of coronary heart disease and diabetes. Coronary heart disease attributed to smoking (105,600) was the highest, followed by stroke (77,200), hypertension (6,000), and diabetes mellitus (5,900). Stroke attributed to drinking (30,700) was the highest followed by coronary heart disease (16,700) and diabetes (1,100). The disease burden caused by smoking and drinking was higher in men (164,000 and 40,700, respectively) than in women (30,700 and 7,300, respectively). Conclusion: There is a high prevalence and significant burden associated with major chronic diseases in Shanxi Province. Therefore, the need for the application of various interventions to control smoking and drinking (the major predisposing factors) should be applied to reduce this burden.